Exercise Training Induces Left- but not Right-sided Cardiac Remodelling in Olympic Rowers - Kleinnibbelink, Geert; Panhuyzen-Goedkoop, Nicole; Hulshof, Hugo; van Dijk, Arie; George, Keith; Somauroo, John; Oxborough, David; Thijssen, Dick H.J. (International Journal of Sports Medicine, 2021)
Whilst the athlete’s heart has been extensively described, less work has focused on the potential for elite athletes to demonstrate further cardiac remodelling upon an increase in training volume. Moreover, little work explored potential side-specific cardiac remodelling. Therefore, we examined the impact of an increase in training volume across 9-months in elite rowers on left- and right-sided cardiac structure, function and mechanics (i. e. longitudinal, radial and circumferential strain, twist and strain-volume loops). As part of the preparations to the 2012 Olympic Games, twenty-seven elite rowers (26.4±3.7years, 19 male) underwent echocardiography prior to and post (9 months) an increase in training volume (24 to 30–35 h weekly). Training increased left ventricular structure, including wall thickness, diameter, volume, mass and LV twist (all p<0.05). Female rowers demonstrated larger adaptation in left ventricular diameter and mass compared to male rowers (both p<0.05). No changes were observed in other measures of left ventricular function in both sexes (all p>0.05). The 9-month intervention showed no change in right ventricular/atrial structure, function or mechanics (all p>0.05). In conclusion, our data revealed that 9-month increased training volume in elite rowers induced left-sided (but not right-sided) structural remodelling, concomitant with an increase in left ventricular twist, with some changes larger in women.
Keywords: athlete’s heart; right ventricle; cardiovascular disease; echocardiography; speckle tracking echocardiography